SOCIAL-PSYCHOLOGICAL PREREQUISITES FOR FORMING THE YOUTH’S SELF-PERFORMANCE - S. Grishaeva; O. Kolosova (Вестник университета)
In the article the questions of forming independency and separation from parent family by modern young people are reviewed. Characteristics of independency are described, reasoning is given that nurturing of independency requires forming of dedication, independency, breadth of views, thinking, flexibility of mind and deals, enterprise and sober analysis of situations and events going on in life. Results of the study of preconditions to forming independency in modern students are given. Preconditions that had been found as a result of the questionnaire, are proved by data from the expert survey.